Long-Term Evaluation of Drivers’ Behavioral Adaptation to an Adaptive Collision Avoidance System - Muslim, Husam; Itoh, Makoto (Human factors, 2021)
Objective Taking human factors approach in which the human is involved as a part of the system design and evaluation process, this paper aims to improve driving performance and safety impact of driver support systems in the long view of human–automation interaction. Background Adaptive automation in which the system implements the level of automation based on the situation, user capacity, and risk has proven effective in dynamic environments with wide variations of human workload over time. However, research has indicated that drivers may not efficiently deal with dynamically changing system configurations. Little effort has been made to support drivers’ understanding of and behavioral adaptation to adaptive automation. Method Using a within-subjects design, 42 participants completed a four-stage driving simulation experiment during which they had to gradually interact with an adaptive collision avoidance system while exposed to hazardous lane-change scenarios over 1 month. Results Compared to unsupported driving (stage i), although collisions have been significantly reduced when first experienced driving with the system (stage ii), improvements in drivers’ trust in and understanding of the system and driving behavior have been achieved with more driver–system interaction and driver training during stages iii and iv. Conclusion While designing systems that take into account human skills and abilities can go some way to improving their effectiveness, this alone is not sufficient. To maximize safety and system usability, it is also essential to ensure appropriate users’ understanding and acceptance of the system. Application These findings have important implications for the development of active safety systems and automated driving.